Desenvolvimento de bebidas fermentadas com coprodutos de frutas com potencial antioxidante - Câmara, Gabriel Barbosa (2022)
In a country where millions of people have nutritional needs, innovative ways of eating, from food sources that are commonly wasted, can be an alternative nutritional source such as the use of agro-industrial by-products. The inclusion of by-products from fruits as a matrix option for the development of beverages can act by enhancing the fermentation process. Therefore, this study aimed to develop fermented beverages using agro-industrial by-products from the processing of tropical fruit pulp. Fruit co-products were submitted to evaluation of the antioxidant capacity, being selected for the development of the formulations the three co-products that obtained the best results (FCA: acerola, FCG: guava and FCT: tamarind). The formulations developed were evaluated for physical-chemical and microbiological parameters and total antioxidant capacity and the fermentation kinetics were evaluated during F1 and F2, using the parameters of Total Titratable Acidity, Total Soluble Solids and pH. The formulations were subjected to in vivo tests (locomotive activity and acute toxicity) and the sensory profile was analyzed in order to verify consumer acceptance. All formulations presented physicochemical parameters in compliance with current legislation. During the fermentation kinetics, it was possible to notice that as the pH and the soluble solids content decreased, the acidity increased, with a final average pH of 3.12 for FCA, 2.85 for FCG and 2.78 for FCT. The acidity was 0.94% for FCA, 0.75% for FCG and 1% for FCT. The formulation that presented the highest content of total soluble solids was FCT (8.17). Among all the formulations, FCA had the best antioxidant potential (19.96±0.77). The kombucha formulations in the present study showed satisfactory microbiological quality. The locomotor activity test in vivo suggests a possible sedative action, such as those caused by benzodiazepines (anxiolytic drugs), which decrease locomotor activity (mobility) of adult zebrafish (Danio rerio) in open field. In addition, all formulations proved to be safe for human consumption (LC50 > 0.25). All formulations showed satisfactory sensory acceptance, with better results for FCG, FCT and FCA, respectively. In view of the results presented, it is possible to perceive that the formulations have an excellent nutritional composition, both being safe for human consumption from a microbiological and toxicological point of view, in which the present study can corroborate the provision of new food alternatives, in addition to the use of fruit co-products.